Conceptual Framework to Support the Design of Innovation Spaces in Universities - Palominos-Belmar, P; Delgado-Cadena, L (Institute of Electrical and Electronics Engineers Inc., 2021)
The innovation spaces are increasingly popular in both the private and public sectors. Companies and universities have bet on the development of these spaces in their different types: Fab Lab, Makerspace, Co-working space, Living Lab, etc. Many universities are currently opting for the construction of a space of these characteristics on their facilities, seeing in this type of space an opportunity to get closer to the industrial sector, but also as a supporting environment for learning and research. In this article, we focus on studying what are the factors that characterize the innovation spaces in universities. We analyze the three basic missions of the university: teaching and learning, research and business services. We then relate the academic mission to the concept of collaborative learning and the business mission to the concept of the academic entrepreneurship . The mission of research, being a recurrent activity in the two associated concepts, is integrated in a parallel way. Subsequently, a conceptual framework is proposed, characterized by the dimensions that make up an innovation space in universities, focused on either the academic mission or the business mission, in order to determine how to design and configure an innovation space in a university to support these two missions. © 2021 IEEE.